2022
DOI: 10.1039/d2ce01017h
|View full text |Cite
|
Sign up to set email alerts
|

Non-covalent interactions of the hydroperoxo group in crystalline adducts of organic hydroperoxides and their potassium salts

Abstract: The present study demonstrates the similarity of hydrogen bonding of hydroperoxo functionality in organic hydroperoxide crystalline adducts (HPCA) and the much larger group of crystalline peroxosolvates. Based on a systematic...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 73 publications
3
4
0
Order By: Relevance
“…64 Moreover, the C-OH group forms H-bonds with H 2 O 2 molecules as a proton donor with lower energy (26 kJ mol À1 ), which is in agreement with the H 2 O 2 and H 2 O hydrogen bonding features in isomorphous peroxosolvates and hydrates. 53,64,91 The energies of XBs are lower than those of H 2 O 2 H-bonds (Table 2 and Tables S5-S7, ESI †). Specifically, the CH 2 -IÁ Á ÁO 2 H 2 XBs are characterized by energy values of 13 and 16 kJ mol À1 , exceeding the value for similar interaction in 3 (10 kJ mol À1 ).…”
Section: Quantification Of Non-covalent Interactions By Bader Analysi...supporting
confidence: 64%
See 2 more Smart Citations
“…64 Moreover, the C-OH group forms H-bonds with H 2 O 2 molecules as a proton donor with lower energy (26 kJ mol À1 ), which is in agreement with the H 2 O 2 and H 2 O hydrogen bonding features in isomorphous peroxosolvates and hydrates. 53,64,91 The energies of XBs are lower than those of H 2 O 2 H-bonds (Table 2 and Tables S5-S7, ESI †). Specifically, the CH 2 -IÁ Á ÁO 2 H 2 XBs are characterized by energy values of 13 and 16 kJ mol À1 , exceeding the value for similar interaction in 3 (10 kJ mol À1 ).…”
Section: Quantification Of Non-covalent Interactions By Bader Analysi...supporting
confidence: 64%
“…62,63 The incorporation of the hydroperoxo group into an organic moiety and its cocrystallization with hydrogen peroxide could be a new option for accumulating a higher energy level in a crystalline material. While H-bonds play a structure-directing role in crystalline peroxosolvates of organic coformers 62,63 and adducts of organic hydroperoxides, 64 XBs, in particular Hal⋯O bonds, can also stabilize crystals, as has previously been shown for a number of energetic cocrystals. 10,65,66…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…There are four oxygen atoms and four hydrogen atoms, forming an eight-membered ring in the conformation of boat-chair via hydrogen bond possessing the lowest transannular strain and energy ( Figure 4 ). 51 , 52 The O … O distances in O–H … O hydrogen bond system range is 2.5627(15)−2.7583(15) Å, relatively shorter than the reported intermolecular O … O distances (2.70–3.00 Å), 53 , 54 suggesting the existence of stronger hydrogen bonds in crystal C1 .
Figure 4 Structure analysis of eight-membered rings of hydrogen bond Selected bond distances (Å): O1-H1 0.89(3), O1–H2 0.86(3), O3–H3 0.86(3), O3–H4 0.90 (3), O4 … H1 1.69(3), O2 … H2 1.97(3), O2 … H3 1.71(3), O4 … H4 1.83(3), O1 … O2 2.7583(15), O2 … O3 2.5627(15), O3 … O4 2.6578(15), O1 … O4 2.5659(15).
…”
Section: Resultsmentioning
confidence: 68%
“…Previously, the similarities of hydrogen bonding between organic hydroperoxides and a large group of crystalline peroxosolvates were reported on the basis of the systematic analysis of the CSD. , It was found that the hydroperoxo group always participated in hydrogen bonding as a proton donor, and this type of hydrogen bonding played a predominant role in the crystal packing. To understand whether hydrogen bonding in antimony dihydroperoxides was governed by the same principles, we analyzed hydrogen bonding networks in the crystal structures of compounds I – VI .…”
Section: Resultsmentioning
confidence: 99%